(untitled) (CIPEEX, 2025)
This comparative review synthesizes evidence from five studies examining the interplay between nutritional status, cardiovascular hemodynamics and whey protein supplementation in severe COPD. Observational data indicate that malnutrition correlates with reduced peak VO₂ and lower O₂ pulse during cardiopulmonary exercise testing, reflecting impaired cardiovascular efficiency (Shan et al., 2015). Biomarker studies demonstrate dysregulation of the endothelial nitric oxide pathway — including increased ADMA/SDMA and altered nitrite/nitrate ratios — which parallels airway inflammation and may underlie systemic vascular dysfunction (Csoma et al., 2019). Randomized interventions using whey-based supplements report consistent gains in fat-free mass, muscle strength and exercise capacity, along with significant reductions in pro-inflammatory cytokines such as IL-6 and TNF-α, with effects amplified when supplementation is paired with pulmonary rehabilitation (Ahmadi et al., 2020; Sugawara et al., 2012; Zong et al., 2023). Despite promising trends, most trials were short (8–12 weeks), included small samples and seldom assessed direct cardiac hemodynamic endpoints such as cardiac output, flow-mediated dilation or heart-rate variability. Collectively, current evidence supports a link between poor nutritional status and adverse exercise-related hemodynamic surrogates, and suggests whey protein can attenuate systemic inflammation and improve functional cardiovascular parameters. Larger, longer randomized studies incorporating direct hemodynamic measures and comprehensive inflammatory profiling are needed to confirm cardioprotective effects.